2013
DOI: 10.1177/1708538113493418
|View full text |Cite
|
Sign up to set email alerts
|

Cause of a rare acute renal insufficiency: Rupture aortocaval fistula

Abstract: After a long-term untreated fistula, right-sided heart failure, acute renal and hepatic insufficiency, deep vein thrombosis and pulmonary thrombo-embolism can be seen in these patients. Increased venous pressure should be the reason for decreased arterial flow results in renal insufficiency. Emergency intervention in these patients saves the patient's life as well as prevents irreversible organ failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…[530][531][532][533] EVAR is preferred, [534][535][536][537][538][539][540] with expected resolution of preoperative heart failure and other physiologic disturbances. [541][542][543][544] If open repair is required, venous bleeding should be anticipated and care taken to minimize the risk of pulmonary air embolism or embolism of thrombotic debris by placement of sponge sticks proximal and distal to the aortocaval fistula for control, followed by direct suture repair of the defect. 545,546 Since 2013, an additional 53 patients presenting with an aortocaval fistula have been added to the previously reported 250 cases.…”
Section: Special Considerationsmentioning
confidence: 99%
“…[530][531][532][533] EVAR is preferred, [534][535][536][537][538][539][540] with expected resolution of preoperative heart failure and other physiologic disturbances. [541][542][543][544] If open repair is required, venous bleeding should be anticipated and care taken to minimize the risk of pulmonary air embolism or embolism of thrombotic debris by placement of sponge sticks proximal and distal to the aortocaval fistula for control, followed by direct suture repair of the defect. 545,546 Since 2013, an additional 53 patients presenting with an aortocaval fistula have been added to the previously reported 250 cases.…”
Section: Special Considerationsmentioning
confidence: 99%
“…Infrarenal aortic aneurysms with the involvement of the right iliac artery seem to be associated with a high risk of perforation into the inferior vena cava (IVC), which might result in the iliocaval fistula. It had been rarely reported that hepatic and renal dysfunction be the main manifestations of AAA and AVF in a critically ill patient (Gregoric et al, 1991;Lau et al, 2001;Simsek et al, 2014). Here, we reported a case of a patient with hepatic and renal dysfunction as the main manifestations of AAA and AVF.…”
Section: Introductionmentioning
confidence: 74%
“…Lau et al (2001) reported a case of an aortoiliac aneurysm with an aortocaval fistula, presenting a moderate degree of renal and hepatic impairment returned to normal merely two days after successfully treated with endovascular stent-grafting. Simsek et al (Simsek et al, 2014) also pointed out that acute renal and hepatic insufficiency could be caused by a long-term untreated fistula as a consequence of increased venous pressure. In our case, acute hepatic and renal dysfunction had developed as a consequence of increased venous pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Other sites are reported including the tracheobronchial walls, kidneys, lacrimal glands, tongue, and mammary glands. When it affects the lungs or the tracheobronchial wall, symptoms may ensue, such as cough, dyspnea, pleuritic pain, and hemoptysis [193][194][195][196][197][198][199][200][201][202][203]. Amyloid composition in SS is usually of AL type (lambda or kappa) light chains, or less commonly, AA amyloid type [192].…”
Section: Amyloidosis In Pulmonary Sjogren's Syndromementioning
confidence: 99%